Status of Coverage of Dtp3 Vaccine and Related Factors, in Children 12-24 Months Old in Tehran - S Dabiran; MA Abbasi Moghadam (Tehran University of Medical Sciences, 2011)
Background and Aim: Vaccination is one of the most important primary prevention and preventing the spread of infectious diseases. DTP3 is commonly used as a criteria for the availability of health services. The purpose of this study was determining vaccination coverage of DTP3 and factors influencing it. Materials and Methods: One thounsed and four hundred fiftey eight children (12-24 month old) from 17th district of Tehran were enrolled in this cross sectional study. In this study, vaccination status of the DTP3 vaccination schedule according to the demographic variables was determined. Information was collected by a questionnaire referring to childrens vaccination card. Sampling method was cluster sampling and included 146 clusters with 10 children in every cluster. Data collected were analyzed using spssv13 software and chi-square and t tests. Results: In this study, 744 girls and 714 boys participated. 1241 patients, (85.1%) cases received their vaccines at the right time. 190 patients (13%) cases had not received the vaccine at the proper time, and 27 patients (1.9 %) were not vaccinated. Between vaccine status and mothers education (p=0.003), fathers education (p=0.012), family income (p=0.003), number of children in the family (p=0.006), birth order (p=0.007), and status of familys medical record in the health center (active - inactive)(p=0.002), significant difference was observed. Conclusion: Although vaccination coverage rate of DTP3 was 98%, more than 13% of cases, did not receive the vaccine at the right time and this constitutes to childhood illness. More research is needed to identify factors influencing no vaccination at the right time.